Treatment of mandibular trauma in a patient victim of a motorcycle accident: clinical case (Research, Society and Development, 2023)
Mandibular fractures are mostly caused by motorcycle accidents, in which men participate significantly more than women. The Northeast region stands out in the occurrence of traffic accidents and thus, the occurrence of mandibular fractures is widely present in the region. The aim of this study was to report the case of a 26-year-old man, victim of a motorcycle accident with an exposed mandibular fracture, and the treatment chosen by the dental team to treat this injury. The patient in question reported pain on palpation in the mandibular region associated with difficulty in mobility, malocclusion and limited mouth opening. The chosen treatment involved the use of a surgical procedure where the patient used an Erich bar to stabilize the fracture and oral and maxillofacial surgery. The choice of breathing method was efficient for treating the patient's injury, ensuring a quick recovery and return of functionality to the diseased region.